Metallurgy at the Crossroads: New Analyses of Copper‐based Objects at Tianshanbeilu, Eastern Xinjiang, China - LIU, Cheng; LIU, Ruiliang; ZHOU, Pengcheng; LU, Chun; YANG, Zengxin; POLLARD, A. Mark; HOMMEL, Peter; MA, Jian; CUI, Jianfeng; BRAY, Peter; TONG, Jianyi; RAWSON, Jessica (Acta geologica Sinica (Beijing), 2020)
Tianshanbeilu is the largest Bronze Age site in eastern Xinjiang, China. Stretching across the entire second millennium BC, it performed a prominent role in connecting the Hexi corridor, Central China and the steppe. A further insight into the metallurgical tradition and the metal supply network is of vital importance to improve our understanding of its multi‐connected nature. This paper offers a new set of chemical and isotopic data on the copper‐based objects at Tianshanbeilu, including alloying elements, trace elements (impurities) and lead isotopes. Combining the concentrations of arsenic and antimony reveals that arsenic was introduced to copper partially due to the use of specific minerals tethrahedrite‐tennantite. Lead isotopes demonstrate that multiple sources of copper were employed at Tianshanbeilu and a majority of them are characterized by common lead, which appears rather different from those of the Central Plains and the Hexi corridor, but highly consistent with local ores. Surprisingly, one object at Tianshanbeilu contains the well‐known highly radiogenic lead. This object undoubtedly marks the westernmost boundary of the distribution of the highly radiogenic lead. We also anticipate that more lead isotopic analyses in NW China will further contribute to the study of the highly radiogenic lead in Central China.